Basic Business Financial Mentoring for MSMEs in Bogor City - Fahmie, Arief; Riyadi, Rizal; Listari, Sinta; Ghaliyah, Nasya; Kusuma, M. Aditya (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Understanding business finance is a fundamental foundation for the sustainability of micro, small, and medium enterprises (MSMEs). However, most MSMEs in Bogor City still lack adequate knowledge and skills in recording, managing, and evaluating their business finances. This community service program aims to provide basic financial training to MSME actors to enhance their performance and business resilience. The methods used included training sessions, transaction recording simulations, and the preparation of simple financial statements. The results showed a 72% increase in participants’ understanding of cash flow recording and income statement preparation. This activity is expected to be the starting point for sustainable financial development among MSMEs in Bogor City